Analisis Penerapan Software Accurate System Pada Siklus Pembelian Perusahaan Manufaktur - Karsam Karsam; M. Fathon; Ulil Fadilah; Putri aisyha (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2024)
This research aims to analyze the implementation of Accurate System software in supporting the efficiency and effectiveness of the purchasing cycle in manufacturing companies. The purchasing cycle is one of the critical processes that affects the smoothness of operations and cost management of the company. In this study, an analysis was conducted on the implementation of the Accurate System software. The research methods used included data collection through interviews, observations, and documentation studies at manufacturing companies. The research results show that the Accurate System is capable of increasing the speed of the purchasing process, reducing the risk of recording errors, and providing accurate and real-time reports for decision-making. However, there are several challenges in its implementation, such as the need for user training and adjustments to the specific needs of the company. These findings contribute to manufacturing companies in optimizing the management of the purchasing cycle through information technology.